Searching for a Younger Self: Time, Music and Ageing Masculinities in the Novel A Visit from the Goon Squad by Jennifer Egan - Zeman, Zdenko; Geiger Zeman, Marija (American & British Studies Annual, 2020)
The idea that literature matters for an understanding of socio-cultural processes and phenomena is confirmed in Jennifer Egan’s inspiring novel A Visit from the Goon Squad. Four decades since the appearance of punk rock music and culture it has become necessary to incorporate issues concerning ageing in the analysis of musical subcultures (Bennet, 2018, Jennings, 2015). The contrasts of past and present, youth and ageing, older and young generations suggest that time is the most important category as an almost invisible, silent, relentless and invincible driving force. This emphasized temporal perspective shows the inevitability and incessancy of changes not only in human lives but also in the ageist world of the music industry.